PENGARUH KUALITAS PELAYANAN TERHADAP NIAT KUNJUNG ULANG KONSUMEN PADA X CARWASH DI KOTA BANDUNG - Meilita Fifarezqina; Agus Hasan Pura Anggawidjaja (Parahyangan Management Science and Practices Student Review, 2025)
In Bandung, the number of private vehicles increases by 11% yearly. With the increases in private vehicle ownership, the need for vehicle maintenance and cleanliness has also increased significantly. Modern people who are increasingly busy tend to look for practical solutions to maintain the cleanliness and appearance of their vehicles. Competition between vehicle washing businesses will also increase rapidly, resulting in different service quality from each vehicle washing business visited. The purpose of this study is to learn more about service quality’s effect on the repeat visit intention of X carwash consumer in Bandung City. This research is an explanatory study with a quantitative approach to determine the effect of service quality on the intention to revisit X carwash Bandung City. Respondent in this study amounted to 100 people selected true and purposive sampling technique with the criteria of individual who have visited and wash their vehicles at X carwash in Bandung City. The questionnaire was use to collect data, which was then analyze using simple linear regression with IBM SPSS version 29. The descriptive analysis found that most respondent did not intended to return to X carwash because the service quality was poor. Based on the coefficient of determination, the service quality of carwash X contributed 40.6% to the intention to revisit. Based on the simple linear regression equation, the service quality of carwash X significantly influences consumer revisit intention at carwash X Bandung City with a coefficient value of 0.175.